The Effectiveness of Songs in Teaching Listening Activities at SMP Negeri 3 Banggai - Abd. Fajar A. Manyangka; Abdul Rabbi Arrasul; Hardianti Hardianti (BABASAL English Education Journal, 2022)
This research is focused to find out about how is the effectiveness of songs that used by the English teachers in teaching listening activities at SMP Negeri 3 Banggai. This research was conducted by using qualitative research. The data was collected by using interview as the instrument of the research. The researcher interviewed the English teachers by using smartphone to record the data. The result found that the English teachers at SMP Negeri 3 Banggai used song as their strategy in teaching listening activities. It is found that songs in their teaching listening activities are to make a quite pleasant atmosphere, even gradually increasing students' vocabulary mastery and students' ability in listening comprehension. In conclusion, song aims to make students more relaxed and easy to accept lessons, as well as improve students' listening skills according to what they have to learn as junior high school students.